Mengatasi Problematika Belajar Sejarah Siswa Menggunakan Metode Think Pair Share - Nahdatul Hazmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the positive effect of the application of the think pair share model on student learning outcomes in history learning in class X SMAN 1 Lareh Sago Halaban.This paper in collecting data using quasi-experimental techniques and also with descriptive, where in addition to the figures obtained also from observations and strengthened by interviews. From the analysis obtained t count = 18.43 and t-table = 1.73 where 1.73 <18.43> 1.73 which means the hypothesis is accepted at the 95% confidence level (α = 0.05). Thus it can be concluded that, there is a positive effect of the model of cooperative learning in the type of think pair share on student learning outcomes in history learning at X SMAN 1 Lareh Sago Halaban. Keywords: Problems, Think Pair Share Learning Models, Learning Outcomes